Peningkatan Kemampuan Motorik Halus Anak Melalui Permainan Slime Di Taman Kanak-Kanak M. Nur Ikhlas - Reni Rahkhamayani; Sari Dewi (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
This study is based on the suble motor of abnormal motor, the cause because the method of use of teachers in teaching less attractive and strategis. As for this research aims to improve the fine motor skiils of children with slime games. This type of research is classroom action research subjects using group be as many as fifteen children, of which nine and six girls. This research was conducted in kindergarden M. Nur Ikhlas Padang Timur in semester II of the 2018/2019 academic year. The technique used is operation and documentation, then it is processed with a percentage technique. As for this study as many 2 cycles, each held 3 meetings. In cycle 2 if the results have reached the minimum regulatory criteria. From the results of the study and discussion, conclusions can be drawn, namely: 1) Through the game slime can improve the motorcycle capability of the child’s child in TK M.Nur ikhlas east padang district. 2) The Slime game, children can squeeze the Slime well, children can form Slime, children can print Slime and children are able to form Slime with various shapes according to the wishes of the children so as to improve the child's fine motor skills. 3) Improve children's fine motor skills in the game Slime by forming can make children more creative in learning. The results of the study showed an increase in Cycle I obtained, there was an increase in fine motor abilities of children, although not yet optimal. In Cycle II the researchers made improvements, so as to obtain maximum results and achieve the Minimum Requirements Kroiteria. This proves that the game Slime, can improve the fine motor skills of children in kindergarten M. Nur Ikhlas, East Padang.Keywords: Early Childhood, Motor Fine, Slime Game